Competition, collusion and spatial sales patterns: Theory and evidence - Matthias Hunold; Kai Hüschelrath; Ulrich Laitenberger; Johannes Muthers (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2018)
This article studies competition in markets with transport costs and capacity constraints. We compare the outcomes of price competition and coordination in a theoretical model and find that when firms compete, they more often serve more distant customers who are closer to the competitor's plant. If firms compete, the transport distance also varies in the degree of overcapacity, but not if they coordinate their sales. Using a rich micro-level data set of the cement industry in Germany, we study a cartel breakdown to identify the effect of competition on transport distances. Our econometric analyses support the theoretical predictions.
Keywords: K21; L11; L41; L61; 330; capacity constraints; cartel; cement; spatial competition; transport costs